Relationship between physical activity and sedentary lifestyle with the incidence of obesity in bri bank malang kawi employees - Aini, Hasna Nabiilah Nur; Tursinawati, Yanuarita; Kurniati, Ika Dyah (Institute of Computer Science (IOCS), 2025)
Lack of physical activity and sedentary lifestyle habits can lead to obesity. Insufficient physical activity may result in decreased energy expenditure in the body, creating an imbalance between energy intake and output during daily activities. This study aimed to analyze the relationship between physical activity and sedentary lifestyle with obesity among employees of BRI Malang Kawi Bank. This research employed an analytical observational design with a case-control approach. Samples were selected using purposive sampling, consisting of 15 obese and 15 non-obese respondents. Physical activity data were collected using the GPAQ questionnaire, while sedentary lifestyle was assessed using the WSQ questionnaire, both completed by the employees in December 2023. Spearman rank correlation analysis was used. Most respondents had sufficient physical activity, with 60% in the obese group and 80% in the non-obese group. Weekend sedentary time was 7.1 hours for obese and 8.9 hours for non-obese respondents. A significant positive correlation was found between physical activity and obesity (p = 0.037), whereas no significant relationship was observed between sedentary lifestyle and obesity (p = 0.952). Physical activity significantly influenced obesity incidence, while sedentary lifestyle had no effect among BRI Malang Kawi Bank employees.